2015
DOI: 10.5415/apallergy.2015.5.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis due to caffeine

Abstract: We report a rare case of anaphylaxis due to caffeine intake. A 27-year-old woman suffered her first episode of anaphylaxis and a positive skin prick test suggested that the anaphylaxis was due to an IgE-mediated hypersensitivity reaction to caffeine. She was diagnosed with caffeine allergy and has not had an allergic reaction after avoiding foods and drinks containing caffeine. Although caffeine is known to have antiallergic effects, this case shows that caffeine can be an allergen and cause anaphylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…[141,142] Caffeine and miscarriage risk Both men and women who consumed at least two caffeinated beverages a day during the weeks prior to conception slightly increased the risks of a miscarriage [143,144] Coffee consumption associated with risk of Allergies. Anaphylaxis due to caffeine [145,146] Caffeine causes more forceful heart contractions Coronary artery disease, the risk may be increased in individuals who with slow metabolizers of caffeine and drink two or more cups of coffee per day. The ingestion of large quantities of caffeine might be associated with arrhythmic and cardiovascular events, especially in patients with underlying heart disease.…”
Section: Health Risks Of Coffee Consumption Mode Of Action Sourcesmentioning
confidence: 99%
“…[141,142] Caffeine and miscarriage risk Both men and women who consumed at least two caffeinated beverages a day during the weeks prior to conception slightly increased the risks of a miscarriage [143,144] Coffee consumption associated with risk of Allergies. Anaphylaxis due to caffeine [145,146] Caffeine causes more forceful heart contractions Coronary artery disease, the risk may be increased in individuals who with slow metabolizers of caffeine and drink two or more cups of coffee per day. The ingestion of large quantities of caffeine might be associated with arrhythmic and cardiovascular events, especially in patients with underlying heart disease.…”
Section: Health Risks Of Coffee Consumption Mode Of Action Sourcesmentioning
confidence: 99%
“…Chin et al [ 13 ] described the cross-reactive hypersensitivity of clopidogrel towards both its fellow thienopyridine, prasugrel, as well as the structurally dissimilar ticagrelor, and its subsequent successful desensitization. Sugiyama et al [ 14 ] described an interesting case of caffeine induced anaphylaxis. Skin prick test showed a positive response to caffeine which suggested that an IgE-mediated mechanism could be involved in this anaphylactic reaction.…”
mentioning
confidence: 99%